Evaluation of novel approaches to software engineering : 9th International Conference, ENASE 2014, Lisbon, Portugal, April 28-30, 2014, Revised selected papers /: 9th International Conference, ENASE 2014, Lisbon, Portugal, April 28-30, 2014, Revised selected papers. (2015) - Unknown
No abstract available